G1. Maternal haemodynamics assessment in preterm delivery: two different haemodynamic profiles. (12th August 2016) - Farsetti, D.; Lo Presti, D.; Pisani, I.; Tiralongo, G. M.; Gagliardi, G.; Vasapollo, B.; Novelli, G. P.; Valensise, H.
Abstract: Introduction : The purpose of our study was to evaluate the maternal haemodynamic profile in women diagnosed with threatened preterm delivery (TPD) in order to understand the possible pathophysiologic mechanism leading to an increased lifetime risk for future cardiovascular disease. Methods : Sixty-eight patients diagnosed with TPD were enrolled and assessed using a non-invasive method (USCOM®) to determine the haemodynamic parameters. Cervix length assessment, vaginal and rectal swabs, blood inflammatory indexes, foetal vessel Doppler velocimetry, gestational age at the delivery and neonatal outcomes were considered. Results : The population was divided into two groups according to the total vascular resistance (TVR) in Group A ≤ 1000 dynes.s.cm −5, and Group B 41 000 dynes.s.cm −5 . C-reactive protein was higher in Group B versus Group A, suggesting a systemic inflammation status. Group B delivered earlier (32 weeks + 4 days versus 38 weeks + 2 days, p  <0.01), and the neonatal outcome was worse in comparison to Group A. There were significantly lower cardiac output, cardiac index, cardiac power, inotropy index and higher PE/KE in Group B versus Group A. Conclusions : Women diagnosed with TPD showed TVR values 41 000. We enrolled patients between 24 and 38 weeks, and the elevated CRP levels present high risk of preterm delivery. Impaired maternal cardiovascular adaptation during pregnancy in these patients might suggest a possible higher risk for future cardiovascular disease.